Direct and indirect burden of COVID-19 on mortality in Spain (2020 to 2022) - Javier Llorca; Inés Gómez-Acebo; Jéssica Alonso-Molero; Miguel Delgado-Rodríguez; Trinidad Dierssen-Sotos (BMC Public Health)
Abstract Background Life expectancy in high-income countries remained lower in 2022 compared to pre-pandemic levels in 2019. This study explores the deficit of life expectancy and excess of years of life lost (YLL) in Spain from 2020 to 2022, assessing both direct effects of infectious diseases and indirect effects of other causes of death. Methods Data on life expectancy and YLL from 2010 to 2022 were obtained from the Spanish Institute for Statistics (INE). Using linear regression, we estimated expected life expectancy and YLL for 2020–2022 under the assumption that pre-pandemic trends (2010–2019) had continued. Results During the first year of the pandemic, Spanish women lost 1.10 years and men lost 1.40 years in life expectancy. By 2022, life expectancy remained lower than in 2019 for both sexes. The excess YLL was similar across 2020 (2.40 million YLL and 5.3 YLL/100 people), 2021 (2.35 million YLL, 5.1 YLL/100 people), and 2022 (2.35 million YLL, 5.0 YLL/100 people). Approximately 70% of this excess was attributable to infectious diseases (87% in 2020, 78% in 2021, and 43% in 2022). Other major contributors to excess YLL included external causes, circulatory diseases, digestive diseases, and endocrine, nutritional, and metabolic diseases, while cancer mortality did not show an excess during the pandemic period. Conclusions Mortality in Spain in 2022 remained elevated compared to pre-pandemic expectations. The contribution of non-infectious diseases to excess mortality increased over time. Trial registration Not applicable.